Pension Reform and Demographic Uncertainty: The Case of Germany - Christian Habermann; Hans Fehr (University of Würzburg, Department of Economics, 2003)
The present paper compares the distributional and risk-sharing consequences of two pension reform proposals in Germany which both aim to improve the sustainability of the current system by introducing demographic variables to the benefit calculation. While the first reform proposes a so-called "sustainability factor" which measures the changes in the dependency ratio, the second reform proposes a so-called "demographic factor" which takes into account the changes in life expectancy. Our simulations indicate that both reforms imply a double burden for currently middle-aged generations and a double relief for future living generations. On the one side, resources are redistributed from currently towards future living generations. In addition, part of the risk from demographic uncertainty is shifted from future living towards currently living middle-aged generations. The reforms differ, however, with respect to the magnitude of the resource distribution and risk implications. Therefore, future generations are much better of with the "sustainability factor", while it is not clear whether middle-aged generations are better off with the "demographic factor" or the "sustainability factor".
Keywords: D58; J11; H55; 330; Stochastic population forecasts; CGE models; pension reform in Germany; Rentenreform; Gesetzliche Rentenversicherung; Versicherungstechnik; Wirtschaftspolitische Wirkungsanalyse; Generationenbeziehungen; Allgemeines Gleichgewicht; Deutschland; Rentenformel